Practical application of total productive maintenance in Japanese industrial manufacturing plants - Minh, Nguyen Đang (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 27 No 5E, 2011)
Abstract. Total productive maintenance (TPM) has been widely applied in many industrial fields, especially in Japanese industrial companies. From a management point of view, this is an activity that involves all members of the company, from company president down to the most junior company employee. From a point of view of economical effectiveness, a company can benefit from implementing company-wide TPM activities, such as, increasing the availability of existing equipment hence reducing manufacturing costs and reducing equipment investment cost. TPM is not just another “program for maintaining machines”. It is a program that can help a company to remain viable and to develop. This paper has reviewed the research relating to TPM world-wide and has found that the practical application of TPM in Japanese industrial plants has not been concretely discussed. The main purpose of this research is to carry out an empirical study on items in the actual manufacturing activities and to point out the practical application of TPM in Japanese industrial plants.   Keywords: Total productive maintenance, kaizen, productive manufacturing, safety, environment.